Does a Patient's Self-Reported Ability to Weightbear Immediately after Injury Predict Stability for Ankle Fractures. Issue 1 (19th August 2016) - Kwon, John; Ghorbanhoseini, Mohammad; Chien, Bonnie Y.; Hofmann, Kurt J.
Category: Trauma Introduction/Purpose: Determining the stability of ankle fractures, particularly for apparent isolated Weber B fibula fractures, can be difficult. While the ultimate goal remains achieving an anatomic mortise, different techniques to predict ankle stability such as stress and weightbearing radiographs have been utilized with variable results. History of injury and the ability to walk after sustaining ankle trauma may be predictive of stability. Therefore, this study seeks to determine whether a patient's ability to fully weight bear immediately after injury is an effective indicator for ankle stability following ankle fracture. Methods: A prospective review was conducted of patients sustaining isolated, unilateral ankle fractures presenting to two level I trauma centers. Aside from demographic data and fracture characteristics, a patient's ability or inability to fully weightbear immediately after injury was elicited by interview at their initial assessment. This information was correlated with their ankle radiographs, which were deemed stable or unstable fractures based on commonly used indices to assess ankle stability. Results: 102 consecutive patients sustaining ankle fractures were included. Mean age was 45. When analyzing the entire cohort, patients who were able to ambulate immediately after injury were 10 times more likely to have a stable ankle fracture than those who could not bear weight (odds ratio (OR) 9.9 (P < 0.001). The positive predictive value (PPV) for being able to fully weightbear as it relates to a stable ankle fracture was 77%. Additionally, inability to weightbear was 89% specific for an unstable fracture. When separately analyzing patients with apparent isolated fibula fractures (n=56), the PPV was 75%, specificity was 83%, while the OR was 5.8 (p=0.003) for those who could fully bear weight having a stable ankle fracture. Conclusion: This study demonstrates that patient's self-reported ability to fully weightbear immediately after injury is a specific and convenient prognostic indicator for ankle stability across a range of ankle fracture subtypes. Future studies can analyze whether initial weightbearing accurately predicts ultimate management and good outcome.